HUBUNGAN ANTARA KUALITAS BIDAN DALAM PELAYANAN ANTENATAL CARE TERHADAP PERSEPSI IBU HAMIL - Citra Hadi Kurniati (Jurnal Infokes, 2020)
Midwives play an important role in the process of health care, especially antenatal care services (ANC). The quality of midwife services determines the success of the service process. The perception of pregnant women when they come for a pregnancy is related to their availability to return to Antenatal Care examination. This study aims to determine the quality of midwives in ANC services on the perception of pregnant women. This type of research uses observational analytic research, where researchers are directed to explain a situation or situation. The time approach used is cross sectional. Analysis was conducted to test the quality of midwives in providing ANC services to the perception of pregnant women. Analysis of the data in research with ordinal and scale variables is non-parametric statistics. Hypothesis testing using the Chi Square Test. The results showed that there was no relationship between the quality of midwives on perceptions of pregnant women with a p value of valeu> 0.05 with an X × count of 0.325. The conclusion of this study is that there is no relationship between the quality of midwives in providing ANC services to the perception of pregnant women